Dukungan Keluarga Dan Kepatuhan Diet Pasien Diabetes Mellitus Tipe 2 Rawat Jalan Di Rumah Sakit Umum Daerah Kota Mataram - Nita Purnaningsih; Suhaema Suhaema; I Nyoman Adiyasa; Aladhiana Cahyaningrum (Poltekkes Kemenkes Mataram, 2017)
Background. World Health Organization (WHO) has predicts increase in the number of people with diabetes in Indonesia from 8.4 million in 2000 to approximately 21.3 million in 2030. Medical Nutrition Therapy (TGM) is key to the success of the overall control glucose, involvement of the team members are doctors, nutritionists, other health workers as well as patients and their families Objective. To the description of family support on adherence diet DM (exact amount, type, schedule) in patients with type 2 diabetes mellitus in egeneral hospital Mataram City. Research Methods. This study is a descriptive observational study with cross sectional design, that total sample was 22 people. The data collected includes the characteristics of the sample and the method of interview respondents, the level of family support using questionnaires, the data rate of consumption with 2x24 hour recall method Research Result: The age samples in this study has over 40 years old (90.9%), with female sex (68.2%), and the level of high school education (50.0%), type of work as a retired civil servants (59.1 %). Counseling frequency less than 2 times (81.8%) and long suffered from diabetes more than 2 years (59.1%), and blood glucose levels are above normal values (72.7%). The level of compliance, 12 (54, 5%) abiding in the amount of energy and carbohydrates, 12 (54.5%), comply with the right kind of foodstuffs and 11 (50%) comply with the recommended proper feeding schedule. Conclusions: Good family support tend to make patients with type 2 diabetes to adhere to the right kind of food and eating schedule, but not affect the compliance of patients with DM in the right amount of energy and carbohydrates.